Clinical Trial of Autologous Dendritic Cell Administration Effect on Water Molecule Diffusion and Anti-Inflammatory Biomarkers in Diabetic Kidney Disease - Paulus Stefanus Dimu; Aziza Ghanie Icksan; Farhat; Jonny; Bhimo Aji Hernowo; Terawan Agus Putranto (Current Issues in Molecular Biology)
Diabetic kidney disease (DKD) significantly increases mortality, with patients facing a fourfold risk of death within ten years. Chronic inflammation, marked by transforming growth factor-β (TGF-β) and intracellular adhesion molecule-1 (ICAM-1) activity, contributes to kidney damage and fibrosis. This study investigates the effect of autologous dendritic cells on inflammation and kidney function, focusing on apparent diffusion coefficient (ADC), TGF-β, and ICAM-1 levels. This quasi-experimental clinical trial involved 22 DKD patients at Gatot Soebroto Army Hospital. Patients received autologous dendritic cell injections. Baseline and post-intervention magnetic resonance imaging (MRI) scans measured ADC values, and ICAM-1 and TGF-β levels were analyzed. Post intervention, the median ADC decreased from 1.75 mm2/s to 1.64 mm2/s (p = 0.223). ICAM-1 levels increased significantly in females (p = 0.04) but not in males (p = 0.35). No significant changes were found in TGF-β levels (p = 0.506). ADC changes were statistically insignificant and did not correlate with CKD severity. ICAM-1 increases in females correlated with improved creatinine levels, suggesting kidney function improvement. Autologous dendritic cell therapy revealed potential gender-specific immune responses but showed limited overall biomarker improvements. Further studies are required to validate its therapeutic value.